Prevalence of canine heartworm disease in the gemlik area, bursa - Turan Civelek; Alparslan Yıldırım; Anıl Iça (Eurasian Journal of Veterinary Sciences)
The purpose of this study was to determine the prevalence of heartworm disease (Dirofilaria immitis) infections in dogs in the Gemlik area, Bursa. This study was carried out between June 2004 and September 2004. A total of 100 dogs with various ages and sexes were included in the study. Of these, 65 were between 0.5 and 2 year old, 25 were 3-6 year old and 10 were over 7 year old. Heparinized blood specimens obtained from dogs were separately examined with native and Modified Knott techniques for the presence of circulating microfilariae while sera were examined with commercial test kit for the presence of circulating antigen. No circulating microfilaria was found in peripheral blood of examined dogs by native and modified Knott techniques whereas parasite antigens were determined in the sera of two male dogs one of which was aged between 3-6 years and the second was over 7 years. In conclusion, the prevalence of Dirofilaria immitis was determined as 2 % amongst dogs in the Gemlik area, Bursa (Occult infection).